Why Do So Many Incompetent Men Become Leaders? - Premuzic, Tomas Chamorro (Harvard Business Review Press, 2019)
In this timely and provocative book, Tomas Chamorro-Premuzic asks two powerful questions: Why is it so easy for incompetent men to become leaders? And why is it so hard for competent people--especially competent women--to advance? Marshaling decades of rigorous research, Chamorro-Premuzic points out that although men make up a majority of leaders, they underperform when compared with female leaders. In fact, most organizations equate leadership potential with a handful of destructive personality traits, like overconfidence and narcissism. In other words, these traits may help someone get selected for a leadership role, but they backfire once the person has the job. When competent women--and men who don't fit the stereotype--are unfairly overlooked, we all suffer the consequences. The result is a deeply flawed system that rewards arrogance rather than humility, and loudness rather than wisdom. There is a better way. With clarity and verve, Chamorro-Premuzic shows us what it really takes to lead and how new systems and processes can help us put the right people in charge.